A Moderated-Mediation Analysis of Organizational Justice and Leader-Member Exchange: Cross-Validation With Three Sub-samples - Shkoler, Or; Tziner, Aharon; Vasiliu, Cristinel; Ghinea, Claudiu-Nicolae (Frontiers in Psychology, 2021)
In an increasingly competitive work world, managers—whose links with subordinates, and their perceptions thereof, are critical components in that relationship—need to monitor employees' mindsets to facilitate their productivity. Our paper investigates organizational justice perceptions as an antecedent to two important outcomes: organizational citizenship behaviors and counterproductive work behaviors. The moderating effect of leader-member exchange and the mediating effect of work motivation were incorporated into a parsimonious moderated-mediation model designed to assist managers in achieving the stated objective. The model was tested on 3,293 Romanian workers, randomly divided into sub-samples of 1,098, 1,098, and 1,097 participants. Indicating high data consistency and credibility for the most part, in each sub-group, all the variables associated as predicted, with the notable exception of LMX. Implications, limitations, and suggestions for future research are discussed, with emphasis on the investigation's cultural context.